PT. erudeye Indonesia’s Pazcal Cloud Launching Activity Report (Project Officer) - Pipin F.P. Lestari; Djoko Setyabudi; Nurrist Surayya Ulfa; Tandiyo Pradekso (Interaksi Online, 2015)
PT erudeye Indonesia is a B2B company with a business model that is established in the information technology and focuses on cloud computing and enterprise services. In 2014, PT. erudeye Indonesia plans to develop cloud computing services Pazcal (Spazio & Scala), spazio means space, scala is scale which is intended for enterprise IT in the Jakarta. PT erudeye Indonesia through Pazcal product want to enter the cloud computing market in Indonesia because Indonesian enterprise needs for a large data storage. But, Pazcal has not received the awareness because the product is still new. Furthermore, cloud providers in Indonesia are also very numerous and varied so that Pazcal must have a difference of positioning. Therefore PT erudeye Indonesia wants to do the right marketing communication activities for the Pazcal product to get attention and has a position of products in the mind of the target market.The goal of marketing communications activities is to foster awareness and create product positioning as efficient and reliable cloud computing products. Pazcal message strategy arranges the analytical survey considerations, competitors, SWOT, and the theoretical framework which will be delivered by multiple tools at three stages of the implementation strategy of positioning. There are the building stage, the stage of providing education and strengthen the positioning stage in the form of online and offline campaign. At building positioning stage, the tools used are the interface design websites, articles, e-books, social media and media relations. Education stage, the tools used are articles, webinars "PaaS for Quick Development, Collaboration & Deployment" and the seminar "Rainbow Rendezvous: Boost Your Experience with Pazcal". While on the strengthen positioning stage, the tools used are a video testimony, webinar "PaaS for Quick Development, Collaboration & Deployment "and the seminar" Rainbow Rendezvous: Boost Your Experience with Pazcal ". Whole of that marketing communications activities are designed to support the goal of launching Pazcal cloud products.